2021
DOI: 10.1016/j.ijcha.2021.100773
|View full text |Cite
|
Sign up to set email alerts
|

Predicting mortality and hospitalization in heart failure using machine learning: A systematic literature review

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…Even though a more complicated model might have better predictive power, than for example a logistic regression model, if it is a black box model it might not allow for this confidence. While explainable and interpretable AI have been a recent focus within the machine learning field, there is still evidence to show that clinicians and patients distrust in machine learning methods prevents greater uptake (Elish, 2018 ; Mpanya et al, 2021 ; Joshi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though a more complicated model might have better predictive power, than for example a logistic regression model, if it is a black box model it might not allow for this confidence. While explainable and interpretable AI have been a recent focus within the machine learning field, there is still evidence to show that clinicians and patients distrust in machine learning methods prevents greater uptake (Elish, 2018 ; Mpanya et al, 2021 ; Joshi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…ML for HF-related tasks has been widely used in many studies, using different kinds of data (e.g., ECG, EHR, etc.) to obtain indications related to the diagnosis or risk analysis [18,19]. A reduced version of the dataset used in this study was utilized in other studies as previously cited in the introductory section.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest in this study is the evaluation of mortality and hospitalization due to HF since it is one of the greatest challenges associated with the disease. In a recent systematic review [18], many ML-based studies were reported to have dwelt on the prediction of these outcomes. The measured Area Under the Receiver Operating Characteristic (AUROC or AUC) curve varied from between 0.47 to 0.84 for hospitalizations, and from 0.48 to 0.92 for mortality predictions.…”
Section: Related Workmentioning
confidence: 99%
“…Numerous prediction tools have been proposed to predict a variety of health outcomes, including diabetes mellitus [ 1 ], hypertension [ 2 ], dyslipidemia [ 3 ], cancer [ 4 ], cardiovascular diseases (CVDs) [ 5 ], and mortality [ 6 ]. Because multiple risk factors usually contribute to the development of these health outcomes, prediction tools that account for the effects of multiple risk factors help stratify individuals according to their risk levels.…”
Section: Introductionmentioning
confidence: 99%